(Razvoj) razmerja med temeljnimi pravicami in svoboščinami ter temeljnimi ekonomskimi svoboščinami ter pravili o konkurenci v pravu EU - Grilc, Peter (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2011)
The article discusses the development of the relationship between fundamental rights and freedoms and fundamental economic freedoms and competition rules in the community law. In this context the development and recent changes in the primary competition law are analyzed as well. Primary sources of community law have not been significantly changed in and since the Lisbon documents. The central question remains the impact of human rights on interpretation and the use of economic freedoms. The analysis starts with the first period with the focus on economic component. The central part of the article is the analysis of decisions in which human rights influenced importantly on the economic freedom; the analysis is based on judgments in ERT via Connolly and Schmidberger to Omega. Finally decisions post-Omega since 2005 are dealt with.
Keywords: European Union; Evropska unija; fundamental rights; human rights; konkurenčno pravo; konkurenca; economic freedoms; človekove pravice; EU Law; competition; ekonomske svoboščine; ECJ; temeljne pravice; pravo EU; jurisprudence; Sodišče EU; sodna praksa